POTENTIALS OF LAKEI ISLAND AS A RESORT IN KUCHING - Noor Azimah, Saptu; Shaik Azahar, Shaik Hussain
This study focuses on the potential of Lakei Island to become one of Kuching's resorts by studying the facilities provided on the island to meet the needs of visitors. The focus of the study is to identify the potential of Lakei Island as a tourist attraction in Kuching, in order to study the infrastructure facilities provided to meet the needs of visitors in Lakei Island, and the latter is to analyze the promotions provided with the appropriate packages for introducing Lakei Island to the public. However, the community's knowledge of the existence of Lakei Island is an issue for this study. Quantitative methods such as distribution of questionnaires to respondents around Bandar Kuching are conducted. In conclusion, the study found that not all communities around Bandar Kuching knew the existence of Lakei Island to visit there and needed a more promoted promotion from Pulau Lakei management.